2021
DOI: 10.1016/j.sdentj.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Apical periodontitis promotes insulin resistance and alters adaptive immunity markers in rats

Abstract: Highlights Periapical lesions promotes higher T-bet expression and lower GATA3 and FOXP3 expression. Periapical lesion promotes increased GATA3 and decreased FOXP3 expression in the group with 4 periapical lesions (4PL) The adaptive immune system, with a predominance of the Th1 polarization, may be involved in the development of insulin resistance in rats with Periapical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Possible mechanisms of interaction between endodontic disease and T2DM have been explored by numerous studies, which could provide several explanations for the findings of some observational studies (Bain et al., 2009; Barcelos et al., 2020; Cintra et al., 2014; Felipe Pereira et al., 2021). Studies have reported that the inflammatory response, which impacts insulin sensitivity, plays a crucial role in the development of diabetes (Bloomgarden, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible mechanisms of interaction between endodontic disease and T2DM have been explored by numerous studies, which could provide several explanations for the findings of some observational studies (Bain et al., 2009; Barcelos et al., 2020; Cintra et al., 2014; Felipe Pereira et al., 2021). Studies have reported that the inflammatory response, which impacts insulin sensitivity, plays a crucial role in the development of diabetes (Bloomgarden, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(2009) established a periapical abscesses model in pregnant rats, they found significant increases of serum TNF‐alpha, blood glucose and serum insulin concentrations in rats with pulpal or periapical abscesses, and concluding periapical abscesses is associated with the development of insulin resistance. Additionally, animal experiments have confirmed that apical periodontitis is associated with higher levels of serum inflammatory cytokines and a more active adaptive immune system, which then leads to the promotion of insulin resistance (Felipe Pereira et al., 2021). Recently, findings from an animal experiment have demonstrated the role of apical periodontitis in changes in antioxidant status and Na+/K+‐ATPase activity, which may be another pathway by which apical periodontitis affects the pathogenesis of type 2 diabetes (Barcelos et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection of AP could cause aggravated and dysregulated inflammatory response, which may result in poor glycemic control and increased insulin requirements ( 49 , 73 , 74 ). Similarly, animal experiments have showed that AP could alter insulin signaling and increase blood glucose concentrations by elevating serum inflammatory cytokines and activating the adaptive immune system ( 74 - 77 ). Maternal alterations in inflammation and insulin signaling pathways caused by AP may directly affect insulin resistance in adult offspring ( 78 ).…”
Section: Metabolic Diseasementioning
confidence: 99%